The role of applying governance on the quality of job performance of workers in education directorates in Al Khalil Governorate - State of Palestine - Amro, Feryal Abdulaziz (Journal of Educational and Psychological Sciences, 2021)
This study aims to know the effect of applying governance on the quality of the job performance of workers in the education directorates, as the study community consists of all workers in the education directorates in the Hebron governorate, and in order to achieve the objectives of the study, the researcher used the descriptive and analytical approach, by building a questionnaire that was applied on the sample of the study consisting of (250) female and male employees, the results showed that the level of governance in the directorates of education in Hebron governorate was moderate, and that the quality of job performance was moderate, and that there was a statistically significant effect of the application of governance on the quality of job performance, and in light of this the researcher recommended a group of Recommendations.